Adaptive Changes in Early and Late Blind: A fMRI Study of Braille Reading - BURTON, H. (2002)
Braille reading depends on remarkable adaptations that connect the somatosensory system to language. We hypothesized that the pattern of cortical activations in blind individuals reading Braille would reflect these adaptations. Activations in visual (occipital-temporal), frontal-language, and somatosensory cortex in blind individuals reading Braille were examined for evidence of differences relative to previously reported studies of sighted subjects reading print or receiving tactile stimulation. Nine congenitally blind and seven late-onset blind subjects were studied with fMRI as they covertly performed verb generation in response to reading Braille embossed nouns. The control task was reading the nonlexical Braille string “######”. This study emphasized image analysis in individual subjects rather than pooled data. Group differences were examined by comparing magnitudes and spatial extent of activated regions first determined to be significant using the general linear model. The major adaptive change was robust activation of visual cortex despite the complete absence of vision in all subjects. This included foci in peri-calcarine, lingual, cuneus and fusiform cortex, and in the lateral and superior occipital gyri encompassing primary (V1), secondary (V2), and higher tier (VP, V4v, LO and possibly V3A) visual areas previously identified in sighted subjects. Subjects who never had vision differed from late blind subjects in showing even greater activity in occipital-temporal cortex, provisionally corresponding to V5/MT and V8. In addition, the early blind had stronger activation of occipital cortex located contralateral to the hand used for reading Braille. Responses in frontal and parietal cortex were nearly identical in both subject groups. There was no evidence of modifications in frontal cortex language areas (inferior frontal gyrus and dorsolateral prefrontal cortex). Surprisingly, there was also no evidence of an adaptive expansion of the somatosensory or primary motor cortex dedicated to the Braille reading finger(s). Lack of evidence for an expected enlargement of the somatosensory representation may have resulted from balanced tactile stimulation and gross motor demands during Braille reading of nouns and the control fields. Extensive engagement of visual cortex without vision is discussed in reference to the special demands of Braille reading. It is argued that these responses may represent critical language processing mechanisms normally present in visual cortex.